2019
DOI: 10.3390/nu11092134
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Adequacy in Preschool Children Attending Family Child Care Homes

Abstract: Limited data is available on the micronutrient intake and adequacy in preschool children enrolled in family child care homes (FCCH). The goal of this paper is to describe the micronutrient adequacy relative to age-specific recommendations of preschool-aged children (aged 2–5 years) attending FCCH in Rhode Island (RI). Dietary data among younger preschoolers (aged 2–3 years), n = 245) and older preschoolers (aged 4–5 years), n = 121) in 118 RI FCCH (N = 366 children) were analyzed. Nutrient adequacy was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…All studies that measured children's dietary intake used the Diet Observation at Child Care methodology ( Table 3 ). Two studies used baseline data from the Keys to Healthy Family Child Care Homes (Keys) intervention ( Benjamin-Neelon et al, 2018 , Tovar et al, 2018a ), one study used follow-up data from the Keys intervention ( Tovar et al, 2018b ) and three studies used baseline data from the Healthy Start/Comienzos Sanos (Healthy Start) intervention ( Cuadrado-Soto et al, 2019 , Ramirez et al, 2020 , Tovar et al, 2020 ). Educators provided food for children in all the studies.…”
Section: Resultsmentioning
confidence: 99%
“…All studies that measured children's dietary intake used the Diet Observation at Child Care methodology ( Table 3 ). Two studies used baseline data from the Keys to Healthy Family Child Care Homes (Keys) intervention ( Benjamin-Neelon et al, 2018 , Tovar et al, 2018a ), one study used follow-up data from the Keys intervention ( Tovar et al, 2018b ) and three studies used baseline data from the Healthy Start/Comienzos Sanos (Healthy Start) intervention ( Cuadrado-Soto et al, 2019 , Ramirez et al, 2020 , Tovar et al, 2020 ). Educators provided food for children in all the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The nutrients that had a lower mean observed density than recommended included vitamin D, calcium and iron. A study by Cuadrado-Soto et al in Rhode Island (US) likewise found the micronutrient intake density to be adequate for most nutrients among preschoolers across two full days of child care [41]. However, intake of some nutrients was of concern including vitamins D, E, K and potassium [41].…”
Section: Baseline Datamentioning
confidence: 99%
“…Child-care centers provide meals and snacks to children, covering up to half of children's daily nutrient intake [33,41,42]. In order to ensure the children receive a healthy meal at the child-care centers, it is important that children are offered meals containing sufficient energy and having the right nutritional composition that contributes to their overall diet.…”
Section: Baseline Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many of these studies have been conducted in childcare centers, and even though FCCHs provide care of a substantial number of preschoolers, studies exploring what children are consuming in FCCHs are limited [42]. While some studies have been conducted in FCCHs, these have assessed overall diet quality and major food groups [12,22,[42][43][44][45], and have not examined the specific food items that contribute to major food groups and have not looked at differences in specific food sources by FCCPs ethnicity. This information is necessary to develop more effective, culturally targeted interventions, training, and education [17,22]; however, research examining the differences in foods between Latino and non-Latino FCCPs is limited.…”
Section: Introductionmentioning
confidence: 99%